Answering Wicked Questions: Dealing With Opposing Truths as a Nursing Associate Professor. (June 2017) - Topp, Robert; Hershberger, Patricia E.; Bratt, Marilyn
Nursing associate professors frequently are confronted with increasing responsibilities and fewer resources. These challenges commonly contribute to declines in job satisfaction and may result in departing academe. This article addresses these challenges by providing answers to four common "wicked questions" experienced by nursing associate professors: (a) How do I decline a request from a supervisor to take on additional responsibilities while continuing to support the mission of the school and advance my own scholarly productivity? (b) How do I handle the workload of multiple doctoral students with a variety of content areas that are different from my own and maintain my own level of productivity? (c) How do I handle expectations for more service, and leadership for the school, university, and professional organizations, yet the teaching and research responsibilities have not changed or have increased? and (d) What are some additional tips to being a more productive nursing associate professor?